Why donors of foreign aid do not coordinate: the role of competition for export markets and political support - Fuchs, Andreas; Nunnenkamp, Peter; Öhler, Hannes (The world economy, 2015)
Development assistance has been criticised for a lack of coordination between aid donors. This paper argues that competition for export markets and political support prevents donor countries from coordinating their aid activities between one another. To test these hypotheses, we perform logit and fractional logit estimations for a large sample of recipient countries and aid activities since the early 1970s. Our empirical results reveal that export competition between donors is a major impediment to aid coordination. Although less conclusive, we also find some evidence that donors' competition over political support prevents them from coordinating aid activities more closely.